2022
DOI: 10.3389/fonc.2022.954329
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of non-coding RNAs in glucose metabolic reprogramming and chemoresistance in colorectal cancer

Abstract: Metabolic reprogramming plays a critical role in colorectal cancer (CRC). It contributes to CRC by shaping metabolic phenotypes and causing uncontrolled proliferation of CRC cells. Glucose metabolic reprogramming is common in carcinogenesis and cancer progression. Growing evidence has implicated the modifying effects of non-coding RNAs (ncRNAs) in glucose metabolic reprogramming and chemoresistance in CRC. In this review, we have summarized currently published studies investigating the role of ncRNAs in glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Accumulated studies have demonstrated that ncRNA-mediated metabolic reprogramming is involved in regulating the chemotherapy resistance and it has been summarized in Fig. 4 [ 7 ]. MiR-488 has been found to promote oxaliplatin and 5-Fu-induced CRC cell apoptosis and inhibit glucose metabolism by targeting PFKFB3 [ 78 ].…”
Section: Ncrnas Effect Cancer Therapeutic Tolerance Through Metabolic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated studies have demonstrated that ncRNA-mediated metabolic reprogramming is involved in regulating the chemotherapy resistance and it has been summarized in Fig. 4 [ 7 ]. MiR-488 has been found to promote oxaliplatin and 5-Fu-induced CRC cell apoptosis and inhibit glucose metabolism by targeting PFKFB3 [ 78 ].…”
Section: Ncrnas Effect Cancer Therapeutic Tolerance Through Metabolic...mentioning
confidence: 99%
“…Non-coding RNAs (ncRNAs) are novel gene regulatory molecules, mainly including miRNAs, long non-coding RNAs (lncRNAs) and circular non-coding RNA (circRNAs) et al In recent years available evidence is increasingly indicating that dysregulated ncRNAs play a significant role in the progression of cancer malignancy through metabolic reprogramming [ 7 , 8 ]. Consequently, there is a pressing need to elucidate the potential regulatory mechanisms of ncRNAs in the cancer metabolic network for the development of carcinogenesis, as this knowledge holds great promise for future prevention and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%